THE INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON CONSUMER PURCHASE DECISIONS AT KFC IN JAKARTA - Yang, Jia-Shan; Wijaya, Septihani Michella; Xie, Jingyu (Transpublika Publisher, 2024)
The business sector has experienced a notable downturn due to the Covid-19 pandemic, resulting in financial setbacks for many companies. The implementation of PPKM has led to a decrease in people's purchasing power as they prefer to cook at home. In response, fast food companies have launched various promotions to restore sales levels and further develop Indonesia's culinary potential. KFC has maintained the top spot as the best-selling fast-food restaurant in Indonesia for more than a decade not only because of its products, but also because of its professional service quality that makes consumers feel at home and continue to choose KFC as their main choice. This research seeks to analyze how the quality of products and services at KFC affects the purchasing choices of customers. The theoretical framework consists of product quality, service quality, and purchasing decisions. With product quality and service quality as independent variables and purchase decisions as the dependent variable, the study concentrated on KFC outlets in Jakarta. Information was gathered from 100 participants through an online survey using Google Forms. Non-probability sampling through a judgment sampling technique was utilized. Findings indicate that both product quality and service quality play a positive role in influencing the purchasing behaviors of KFC customers in Jakarta. The study concludes that the quality of products and services at KFC in Jakarta significantly impacts customers' purchasing decisions.